Ball-sport endurance and sprint test (BEAST90): validity and reliability of a 90-minute soccer performance test - Williams, J. D.; Abt, G.; Kilding, A. E. (The Journal of Strength and Conditioning Research, 2010)
The aim of this study was to determine the validity and reliability of a 90-minute soccer performance test: Ball-sport Endurance and Sprint Test (BEAST90). Fifteen healthy male amateur soccer players participated and attended 5 testing sessions over a 10-day period to perform physiologic and soccer-specific assessments. This included familiarization sessions and 2 full trials of the BEAST90, separated by 7 days. The total 90-minute distance, mean percent peak heart rate (HRpeak), and estimated percent peak oxygen uptake of the BEAST90 were 8,097 ± 458 m, 85 ± 5% and 82 ± 14%, respectively. Measures obtained from trial 1 and trial 2 were not significantly different (p > 0.05). Reliability of measures over 90 minutes ranged from 0.9-25.5% (% typical error). The BEAST90 protocol replicated soccer match play in terms of time, movement patterns, physical demands (volume and intensity), distances, and mean and HRpeak values, as well as having an aerobic load similar to that observed during a soccer match. Reproducibility of key physical measures during the BEAST90 were mostly high, suggesting good reliability. The BEAST90 could be used in studies that wish to determine the effects of training or nutritional interventions on prolonged intermittent physical performance